PENGARUH REBUSAN DAUN SIRIH TERHADAP PENURUNAN TEKANAN DARAH PADA LANSIA HIPERTENSI - wasis Eko Kurniawan; Wahyu Dianto (Yakpermas Press, 2024)
In society, hypertension is an illness that is rarely under control. When it is, however, it can lead to heart attacks and strokes. In this study, a decoction of soursop and betel leaves was utilized as a therapeutic technique to reduce blood pressure. The purpose of this study is to ascertain how boiling betel leaves affects blood pressure. This kind of study uses a non-equivalent control group research design and is quasi-experimental. Twenty samples were utilized as the sample size. Total Sampling is the sample income approach. The results of the Wilcoxon Test, which produced an analysis of the betel leaf decoction with a systole p-value = 0.005, less than 0.05, and the Paired Samples Test, whose diastole p-value = 0.000 is less than 0.05, also had an impact on the betel leaf therapy group to lower blood pressure in elderly people with hypertension. The study's conclusion is that betel leaf infusion helps elderly hypertension patients' blood pressure go down.